Let me be Frank with you [compact disc, unabridged] - Ford, Richard, 1944- (Ford, Richard, 1944- Frank Bascombe book., 2014)
In the aftermath of Hurricane Sandy, Frank Bascombe travels to the site of his former home on the shore, visits his ex-wife, who is suffering with Parkinson's, and meets a dying former friend.